Portable Health Monitoring Device for Electrocardiogram and Impedance Cardiography Based on Bluetooth Low Energy (Journal of Fiber Bioengineering and Informatics, 2014)
Portable health monitoring device could benefit the life quality of patients as well as decreasing healthcare costs. Monitoring Electrocardiogram (ECG) and Impedance Cardiography (ICG) simultaneouslycan help evaluate cardiovascular disease comprehensively. However most of the ICG monitoring devicesare only used in clinical measurement instead of family monitoring. Based on the above concern, thispaper designed a portable health monitoring device based on Bluetooth Low Energy (BLE) whichis valued for its ultra-low power consumption for long-term continuous non-invasive cardiac activitymonitoring by measuring ECG, ICG, acceleration and angular acceleration of body. There are mainlyfour advantages of this device: 1) High integration: ECG, ICG, acceleration and angular acceleration canbe monitored in a single circuit; 2) Low power consumption: The device can monitor continuously forover 83 hours when powered by a 3.7 V lithium polymer battery with 1000 mAh; 3) Small size: The areaof the PCB is only 30 mm × 40 mm, so it is very easy to be attached to clothes; 4) Wireless communication:The acquired data can be transmitted to a personal computer or a smart phone wirelessly via Bluetooth.Different body postures (upright or supine) can result in change of ICG signal, which can be used foradjusting patients' hemodynamic parameters.